Pharmacokinetic modeling of morphine and its glucuronides: Comparison of nebulization versus intravenous route in healthy volunteers - Thomas Duflot; Tony Pereira; Marie‐Pierre Tavolacci; Robinson Joannidès; Frédéric Aubrun; Fabien Lamoureux; Virginie Eve Lvovschi (Wiley, 2022)
Abstract Intravenous (i.v.) morphine is a safe, robust, and recommended treatment for severe pain using the titration principle. Despite its high efficacy, it is impacted by organizational constraints related to venous access. Nebulized (NEB) morphine may represent an alternative for titration but pharmacokinetic (PK) properties of short nebulization using routine devices need evaluation. Twenty‐seven healthy volunteers were included to receive NEB or i.v. morphine administration using increasing amounts according to Dixon's reference method. Plasma morphine, morphine‐3‐glucuronide (M3G), and morphine‐6‐glucuronide (M6G) were quantified. PK modeling and simulations were performed using Monolix. Dixon's method exhibited a significantly higher morphine dose regimen in the NEB group versus the i.v. group (6.2 [5.3-7.1] vs. 3.0 [2.0-4.0] mg, p < 0.001). Morphine, M3G, and M6G dose‐normalized exposure were significantly lower in the NEB group versus the i.v. group: morphine (19 [13-23] vs. 1044 [702-1266] µg min/L, p < 0.001), M3G (245 [162-287] vs. 3752 [2487-5165] µg min/L, p < 0.001) and M6G (28 [21-43] vs. 466 [370-723] µg min/L, p < 0.001). The model that best fitted the data consisted in a transit compartment for morphine absorption, three compartments for morphine distribution followed by multiple transit compartments (8.2 and 57.5‐min transit time for M3G and M6G, respectively) and a first order elimination for M3G and M6G. Morphine bioavailability in the NEB group was 3.5% using the i.v. group as reference. Administration route and sex significantly influenced morphine and metabolite PKs. This work aimed to evaluate the PKs of NEB morphine compared with the i.v. route. Despite a bioavailability to improve, NEB morphine administration using a routine device is suitable to plan morphine titration.